A Multidimensional Approach to Medication Selection in the Treatment of Children and Adolescents with ADHD - Turgay, Atilla (Matrix Medical Communications, 2007)
The objective of this paper is to outline clinical patient characteristics to individualize medication selection for children and adolescents with ADHD. The treatment guidelines and clinical parameters outlined in this paper are based on clinical research and evidence- and/or consensus-based guidelines for medication treatment of children and adolescents with ADHD and associated symptoms or comorbid disorders. Recommendations are made for medication selection in different clinical situations. The increased availability of ADHD medications over the past few years has provided a number of treatment options with longer symptom control and improved the remission or “multidimensional normalization” for ADHD patients. Selection of the most appropriate medication(s) for complicated cases may present a serious challenge in some situations. This paper outlines selected complicated cases and treatment options.